Developing a Grammar-based ComparativeApproach to English Learning in Higher Education Using the ADDIE Model - Efendi, Rachmat; Setyawan, Slamet; Widyastuti, Widyastuti (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study seeks to develop English language learning materials through the ADDIE model, emphasizing a grammar-based comparative approach to strengthen students’ communicative competence. The primary objectives are to design effective instructional materials and explore the link between grammatical mastery and communication skills. The methodology employs the ADDIE framework to systematically design, implement, and assess materials aligned with students’ learning needs. Findings indicate that incorporating grammatical understanding into language instruction significantly improves both spoken and written fluency. In contrast, limited grammar proficiency can lead to unclear and ineffective communication. The study concludes that grammatical competence plays a crucial role in achieving effective communication, positioning the ADDIE model as a practical and structured tool for material development. This research contributes to the enhancement of foreign language instruction in higher education by proposing an integrative model that connects grammatical and communicative competence. It is expected to particularly benefit students from non-language disciplines by enriching their English learning experience.